Realignment osteotomy of the knee allows for return to work and sport activities in the young athletic population. Issue 4 (19th June 2018) - Witjes, Suzanne; Wanlin, Stacey; Litchfield, Robert; van Geenen, Rutger C I; Kerkhoffs, Gino M M J; Getgood, Alan
Abstract : Objective: To evaluate return to work and sport rates of young athletic patients following knee osteotomy, including the highest level of sports participation and satisfaction with activities. Methods: We performed a cross-sectional study of patients of age 45 years or younger who underwent realignment osteotomy of the knee between 2005 and 2015. Data concerning work activities, sports participation and satisfaction were collected by a survey including the modified Naal and Weiss questionnaires, Numeric Rating Scale (NRS) of satisfaction and Net Promoter Score (NPS). Results: Analysis of data from 60 patients with a median age of 38 (15–45) was performed. Of those 60 patients, 95% returned to sports following surgery, of whom 74% could return to their main preinjury sport or to a different sport of higher impact. The main preoperative sport types involved 65% high-impact, 23% intermediate-impact and 12% low-impact activities. The highest level of sport participation preoperatively was 13% professional, 7% varsity and 80% amateur (58% competitive, 42% recreational). Postoperatively 5% returned to professional level, 4% varsity and 91% amateur (14% competitive, 86% recreational), and at follow-up 22% of patients had retired from sports. At follow-up 88% of patients were still working, with 61% at the same activity level and 12% at a higher level than before surgery. The median NRS satisfaction score with activities in general was 6 (0–10), and with activities of daily living, work and leisure time 9 (0–10), 7 (0–10) and 6 (0–10), respectively. The main reasons for dissatisfaction were persisting knee pain (67%) and lack of range of motion (29%). The NPS was 14, indicating that patients would recommend the surgery to friends or family. Conclusion: Young athletes can return to work and sport activities following realignment osteotomy of the knee. Although their levels of sports participation significantly decreased and satisfaction with their activity level was limited, we disagree with the opinion that a knee osteotomy directly leads to the end of an athlete's sporting career. Level of evidence: Level III, prospective cohort study.